Aulacophoroides (Sternorrhyncha: Aphididae), a generic account, description of a new species from Hong Kong (China) and a key to species - Qiao, Gexia X.; Jiang, Liyun Y.; Martin, Jon H. (Zootaxa, 2006)
The aphid genus Aulacophoroides Eastop and Hille Ris Lambers is reviewed. Aulacophoroides millettiae sp. nov. is described from Millettia sp. in Hong Kong, China. A key to the described species of Aulacophoroides is provided. The type specimens studied are deposited in the Zoological Museum, Institute of Zoology, Chinese Academy of Sciences, Beijing, China and the Natural History Museum, London, U.K.